A nondestructive mechanoelectrical method for determining the strength of concrete under variable temperature and humidity conditions - Fursa T. V. Tatyana Viktorovna (2009, 2009)
An algorithm for the mechanoelectrical nondestructive method for determining the mechanical strength of concrete is developed. The proposed method based on the phenomenon of mechanoelectrical transformations has a higher accuracy of determining the mechanical strength than the accuracy inherent to the sclerometry method, which is applied in practice, and can be used in tests of materials under different temperature and humidity conditions